The Influence of Microbia Time and Types of PGPR on Growth of Soybean Plant (Glycine Max Meril) on Vegetative Phase - Bukhari; Rudi Fadhli; Nuryulsen Safridar (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This research was conducted in the Experimental Garden of the Faculty of Agriculture, Jabal Ghafur Glee Gapui University, Pidie Regency, which took place from September 16 to November 15, 2017. This study used a Completely Randomized Design (CRD) of 2 x 3 with 3 replications. The time factor for administration consists of 2 levels : W1 (Pagi), W2 (Sore). Plant Growth Promoting Rhizobacteria (PGPR) type factors consist of three levels: P1 (Rhizobium), P2 (Mikoriza), P3 (Mikoriza + Rhizobium). Parameters observed in soybean plant components include: plant height at ages 15, 30 and 45 HST, root fresh weight, root dry weight, number of nodulations. The difference in the time of administration of PGPR has a very significant effect on root dry weight, but it does not significantly affect the height of plants aged 15, 30 and 45 HST, root fresh weight, root length and number of root nodules, the best treatment was encountered at the time of administration of PGPR W2 (Afternoon ). Different types of PGPR have very significant effect on root length and number of nodulations, but no significant effect on plant height aged 15, 30 and 45 HST, root fresh weight and root dry weight. The best treatment was found in the treatment P1 (Rhizobium). There was no interaction between the time of administration of the PGPR and the type of PGPR against all observed parameters.